2015
DOI: 10.1016/j.urology.2015.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Urological Surveillance and Medical Complications after Spinal Cord Injury in the United States

Abstract: Objectives To evaluate national patterns of urologic follow up after SCI and the occurrence and predictors of urological complications. Methods This retrospective cohort study utilized a 5% sample of Medicare data 2007–2010. The minimum adequate urologic surveillance was defined as a: urologist visit; serum creatinine; and upper urinary tract imaging study within the two year period. Each patient was classified to their most severe complication in a multivariate linear regression model. Results Among the 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 16 publications
0
17
0
1
Order By: Relevance
“…Other studies have also demonstrated a poor adherence among other populations to urologic screening: among 7,162 patients with SCI in the USA, only 25% of patients received a urologic clinical assessment, serum creatinine analysis, and renal imaging study over a 2-year period; cystoscopy and urodynamics were only performed among 12% and 7%, respectively. 27 …”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also demonstrated a poor adherence among other populations to urologic screening: among 7,162 patients with SCI in the USA, only 25% of patients received a urologic clinical assessment, serum creatinine analysis, and renal imaging study over a 2-year period; cystoscopy and urodynamics were only performed among 12% and 7%, respectively. 27 …”
Section: Discussionmentioning
confidence: 99%
“…[53][54][55] Typically, surveillance protocols suggest either on-demand or regularly scheduled UDS, upper tract imaging, and cystoscopy but there is little consensus on specific approach [3][4][5]56 Consequently, practice patterns vary with regard to the type and frequency of studies used in NLUTD surveillance. [56][57][58][59] Our suggested approach for NLUTD stratifies patients based on their urological risk factors and specific investigations are recommended.…”
Section: Surveillance Studies For Nlutd Patients In the Community Settingmentioning
confidence: 99%
“…While historically used for concerns of increased bladder cancer risk, cystoscopy can be a valuable tool in the evaluation of urethral or bladder integrity and can provide an estimate of external sphincter function. The value of surveil-Guideline: Neurogenic bladder lance cystoscopy for bladder cancer surveillance in the SCI population was addressed in a recent systematic review by Cameron et al 57 The investigators believed that the incidence of bladder cancer was too low to be well-evaluated in these studies, and screening cystoscopy and biopsy did not fit the criteria for a screening test of the general NLUTD population. Patients with prior augmentation cystoplasty have historically been followed with yearly surveillance cystoscopy due to increased risk of bladder cancer.…”
Section: Cystoscopymentioning
confidence: 99%
“…Furthermore, there is no consensus if sUDS should be scheduled regularly or repeated for new patient symptoms or imaging changes. Consequently, practice patterns vary with regard to sUDS frequency (11)(12)(13)(14)(15)(16)(17) and health-care utilization data suggests low uptake of sUDS utilization in NLUTD within the United States and Canada (18,19) .…”
Section: Introductionmentioning
confidence: 99%